Numerical investigation of rain droplet impact on offshore wind turbine blades under different rainfall conditions: A parametric study. (1st June 2020) - Verma, Amrit Shankar; Castro, Saullo G.P.; Jiang, Zhiyu; Teuwen, Julie J.E.
Abstract: The leading edge of a fiber composite wind turbine blade (WTB) is prone to erosion damages due to repeated rain droplet impact during its service life. Such damages are critical to the blade's aerodynamic as well as structural performance, ultimately resulting in substantial repair costs. An effective design of a coating material for WTB is necessary and its analysis must include variables associated with erosive rain droplets such as (1) droplet diameter, (2) impact velocity, and (3) droplet impact angle. The present paper develops and validates a coupled fluid structure interaction (FSI) computational model for simulating rain droplet impact on WTBs, where the structure domain is modelled using conventional finite element method (FEM) and the fluid domain is modelled using smooth particle hydrodynamics (SPH). The 3D numerical model, developed in LS-DYNA, is validated with published experimental results. Further, a parametric study is considered to understand the effects of varying droplet size, impact angles and impact velocities on the impact responses of the leading edge coating system subjected to different rainfall conditions. The rainfall conditions considered for the analysis correspond to four different rainfall intensities ( I ) – light rainfall ( 2 mm/hr ), moderate rainfall ( 10 mm/hr ), heavy rainfall ( 25 mm/hr ), and very heavy rainfall ( 50 mm/hr ). The results show that the impact responses on the coating system increase with increasing droplet size and increasing droplet impact angle with maximum impulses, stresses and damages developed for normal impingement ( 90 ° ). Also, the effects of droplet impact angles in the range of 50 ° to 90 ° are found critical for rainfall intensities representing very heavy rainfall conditions ( I > 25 mm/hr ). The results of the peak contact forces and impulses for the above combination of variables used in the numerical study are found in satisfactory agreement with analytical formulations developed through published experiments. Finally, repetitive rain droplet impact analyses are considered and number of impacts required for onset of erosion damages are found to increase by more than seven times upon reducing impact velocities from 140 m/s to 80 m/s for very heavy rainfall conditions ( I > 25 mm/hr ). The present study is expected to deliver a validated numerical model that can contribute towards enhancing the erosive capacity of a WTB.